2006
DOI: 10.1200/jco.2005.02.7938
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Serum B-Lymphocyte Stimulator Levels in Patients With Familial Lymphoproliferative Disorders

Abstract: Our data suggest serum BLyS levels are elevated in patients with familial B-CLL and that elevated BLyS levels correlate with the presence of a T at -871 in the BLyS promoter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
86
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 82 publications
(94 citation statements)
references
References 23 publications
7
86
1
Order By: Relevance
“…We performed restriction fragment length polymorphism analysis to evaluate the BAFF promoter genotype. The primers used for BAFF promoter amplification were 5Ј-GGCACAGTCAACATGGGAGT-3Ј (forward) and 5Ј-GCTAAGTGTTTTAGCATTGAATTG-3Ј (reverse) as previously described (6). The PCR products were subjected to a restriction enzyme-based screening of the Ϫ871 C/T using 20 units of Bsr BI restriction enzyme.…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…We performed restriction fragment length polymorphism analysis to evaluate the BAFF promoter genotype. The primers used for BAFF promoter amplification were 5Ј-GGCACAGTCAACATGGGAGT-3Ј (forward) and 5Ј-GCTAAGTGTTTTAGCATTGAATTG-3Ј (reverse) as previously described (6). The PCR products were subjected to a restriction enzyme-based screening of the Ϫ871 C/T using 20 units of Bsr BI restriction enzyme.…”
Section: Patientsmentioning
confidence: 99%
“…BAFF, a tumor necrosis factor ␣ (TNF␣) family member, is a key regulator of B cell differentiation, survival, and Ig secretion, and alterations in its expression have been initially associated with different autoimmune disorders, such as Sjögren's syndrome, SLE, and RA (5). Overexpression of BAFF in monocytes has been associated with the presence of a T allele at the polymorphic site Ϫ871 C/T of its promoter in patients with RA and familial lymphoproliferative disorders (6).…”
mentioning
confidence: 99%
“…1 Alkylating agents have long been considered to be part of the cause. [2][3][4][5] Some, but not all, smaller investigations have reported that higher cumulative melphalan dose and longer duration of melphalan therapy are associated with an increased risk of AML. 6,7 The role of nontreatmentrelated factors is largely unknown.…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…4 This indicates that a single genetic variation might affect TACI activation by increasing BLyS levels. Whereas the rs3803800 G SNP in the APRIL gene is nonsynonymous and directly induces amino-acid changes (N96S), the rs11078355 T SNP in the TACI gene is synonymous (S277S).…”
mentioning
confidence: 99%
See 1 more Smart Citation